The Hartman-Wintner Law of the Iterated Logarithm for Noncommutative Martingales - Osu, Bright O; Uzoma, Philip U (International Journal of Mathematical Research, 2016)
In this study, we prove one of the fundamental strong laws of classical probability theory, the Hartman-Wintner’s law of the iterated logarithm for non-commutative martingale using a simple exponential inequality.